Enhancing Business Accountability through Effective Pension Fund Accounting and Reporting - Bela Harti Pratiwi; Aqwa Naser Daulay; Hendra Hermain (Journal of Applied Business Administration, 2025)
The purpose of this study was to describe the implementation of PSAK No. 18 accounting and reporting of retirement benefit programs at DAPENBUN Regional 2 Medan. This research is qualitative in nature using observation, in-depth interviews with various parties in DAPENBUN, and documentation studies of the financial statements for 2023-2024. The data were analyzed descriptively based on four aspects of PSAK No.18, namely recognition, measurement, presentation, and disclosure. The conclusion shows that most of the provisions have been implemented, but there are some obstacles in disclosing financial risks, membership details, and the identity of the independent actuary. These findings are expected to be the basis for improving pension fund reporting in the future. This research contributes through a comprehensive implementation that not only assesses formal compliance but also accountability to pension funds. The findings and recommendations can be used as a reference for improving the reporting and management of pension funds in accordance with PSAK No.18. This research only covers one pension fund institution and has not examined a wider range of stakeholders or cross institutional comparisons .